TOI-431/HIP 26013: A super-Earth and a sub-Neptune transiting a bright, early K dwarf, with a third RV planet - Osborn, Ares (2021)
We present the bright (Vmag = 9.12), multiplanet system TOI-431, characterized with photometry and radial velocities (RVs). We estimate the stellar rotation period to be 30.5 ± 0.7 d using archival photometry and RVs. Transiting Exoplanet Survey Satellite (TESS) objects of Interest (TOI)-431 b is a super-Earth with a period of 0.49 d, a radius of 1.28 ± 0.04 R, a mass of 3.07 ± 0.35 M, and a density of 8.0 ± 1.0 g cm-3; TOI-431 d is a sub-Neptune with a period of 12.46 d, a radius of 3.29 ± 0.09 R, a mass of 9.90+1.53-1.49 M, and a density of 1.36 ± 0.25 g cm-3. We find a third planet, TOI-431 c, in the High Accuracy Radial velocity Planet Searcher RV data, but it is not seen to transit in the TESS light curves. It has an Msin i of 2.83+0.41-0.34 M, and a period of 4.85 d. TOI-431 d likely has an extended atmosphere and is one of the most well-suited TESS discoveries for atmospheric characterization, while the super-Earth TOI-431 b may be a stripped core. These planets straddle the radius gap, presenting an interesting case-study for atmospheric evolution, and TOI-431 b is a prime TESS discovery for the study of rocky planet phase curves.